2015
DOI: 10.1186/s13662-015-0546-z
|View full text |Cite
|
Sign up to set email alerts
|

Discrete-time bifurcation behavior of a prey-predator system with generalized predator

Abstract: In the present study, keeping in view of Leslie-Gower prey-predator model, the stability and bifurcation analysis of discrete-time prey-predator system with generalized predator (i.e., predator partially dependent on prey) is examined. Global stability of the system at the fixed points has been discussed. The specific conditions for existence of flip bifurcation and Neimark-Sacker bifurcation in the interior of R 2 + have been derived by using center manifold theorem and bifurcation theory. Numerical simulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Lemma 2.2. [15,17,22,34] Assume F (λ) = λ 2 + Bλ + C, where B and C are two real constants and let F (1) > 0. Suppose λ 1 and λ 2 are two roots of F (λ) = 0.…”
Section: Stability Analysis and Fixed Points Of The Systemmentioning
confidence: 99%
“…Lemma 2.2. [15,17,22,34] Assume F (λ) = λ 2 + Bλ + C, where B and C are two real constants and let F (1) > 0. Suppose λ 1 and λ 2 are two roots of F (λ) = 0.…”
Section: Stability Analysis and Fixed Points Of The Systemmentioning
confidence: 99%
“…where |c| << 1 represents a small perturbation in c 1 . Assume that (x * , y * ) = denotes fixed point for (14).…”
Section: Neimark-sacker Bifurcationmentioning
confidence: 99%
“…Zhao et al [13] reported flip bifurcation and Neimark-Sacker bifurcation for a class of discrete prey-predator interaction. Singh et al [14] explored local dynamics and bifurcation analysis for a class of Leslie-Gower type predator-prey model with predator partially dependent on prey. Asheghi [15] discussed plant-herbivore type predator-prey interaction for non-overlapping generations.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Liu and Xiao [5] presented complex dynamics for a discrete Lotka-Volterra system after implementation of Euler method. For a similar type of investigations related to predator-prey systems the interested reader is referred to [6][7][8][9][10][11][12][13][14][15][16][17]. All these studies reveal that the discrete predator-prey models with implementation of Euler approximation are dynamically inconsistent with their continuous counterparts.…”
Section: Introductionmentioning
confidence: 99%